2013
DOI: 10.4236/as.2013.412092
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of the interaction of common black bean group genotypes with the environment

Abstract: The purpose of this paper was to assess which environmental factor(s) (location, sowing season or years) in the common black bean genotypes interaction was more expressive and to verify the existence of genotypes with broad and/or specific adaptations to sowing season. Data of grain yield of thirteen genotypes were tested in twelve trials of value of cultivation and use during 2003 and 2004 in the south-central region of Brazil. Analyses of variance were performed with the decomposition of genotypes × environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Ramalho et al (1998) reported similar R 2 values for these interactions. However, Pereira et al (2011) and Torga et al (2013a, 2013b showed that the G×Y interaction is more important than the G×L interaction. In general, there is wide variation in the importance of these two sources of variation, depending on the respective study areas, locations and years, which explains why there is no consensus on which source is the most important.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Ramalho et al (1998) reported similar R 2 values for these interactions. However, Pereira et al (2011) and Torga et al (2013a, 2013b showed that the G×Y interaction is more important than the G×L interaction. In general, there is wide variation in the importance of these two sources of variation, depending on the respective study areas, locations and years, which explains why there is no consensus on which source is the most important.…”
Section: Resultsmentioning
confidence: 98%
“…In works on common bean breeding conducted in Paraná/Santa Catarina and Goiás/Distrito Federal, respectively, Pereira et al (2010cPereira et al ( , 2011 showed that the sources of variation for lines and years were more important than those for locations. Torga et al (2013aTorga et al ( , 2013b) also conducted studies in the above-mentioned States, showing increased…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…in F4 families with the highest mass of seeds per plant (MSP.F4). These distortions in association between traits are due to genic events determinant for their expression, as these traits express quantitative inheritance, low heritability and high influence of the environment (Melo et al, 2007;Pereira et al, 2012Torga et al, 2013). Furthermore, it is notorious that in initial generations of breeding, there is predominance of non-additive effects, which can result in biases in the inferences about superior genotypes.…”
Section: Linear Associations Between Traits Of Agronomic Interestmentioning
confidence: 99%